PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TAI (TEAM ASISSTED INDIVIDUALIZATION) BERBANTUAN VIDEO TERHADAP HASIL BELAJAR SISWA PADA SUB MATERI KONFIGURASI ELEKTRON KELAS X SMA NEGERI 5 PONTIANAK - Yumna Yumna; Cawang Cawang; Dini Hadiarti (Jurnal Ilmiah Ar-Razi, 2017)
ABSTRACTThe proces of chemistry learning in SMAN 5 Pontianakstill used lectures method which was not allowed the students to be active in learning chemistry. Therefore this research aimed toinvestigates the difference of students. Learning achievement and the effect size of the used of cooperative learning type TAI with video to help students learn the electron configuration material. The method of this research was quasi experimental non equivalent control group design. The sample was chosen using saturated sampling. The technique of data collecting was essay test with validation value 1. The test showed that the reliability coefficient was 0,057 which scored as moderate and worth to be used as research instrument. The hypothesis testing showed that Zvalue = 2,824 which means that the alternative hypothesis Ha was accepted. The effect size results was 21,57%. Bases in the results above the used of cooperative learning type TAI with video was effective to increase students learning achievement of electron configuration material.Keywords: Outcomes Learning, Team Assisted Individualization (TAI) Video, ElectronConfiguration.